White Spot Disease in Black Tiger Shrimp (Penaeus Monodon Fab.) : Infection of White Spot Virus at 20, 100 and 200 uG/Ml by Dipping Method within 120 Minutes Exposure Time - M. Alifuddin; D. Dana; M. Eidman; M.B. Malole; F.H. Pasaribu (Jurnal Akuakultur Indonesia)
An infection trial of white spot disease on tiger shrimp was conducted by water borne inoculation with the different of  viral concentration. The result showed that the viral concentration influenced the appearance of white spot specific lesion, occurrence and disease development. This study also indicated that white spot virus infect hepato-pancreatic tissue as well as gill, intestine and lymphoid tissues.